Defining the Overall Quality of Cowpea‐Enriched Rice‐Based Breakfast Cereals. Issue 1 (12th September 2016) - Marengo, Mauro; Baffour, Leonora C.; Buratti, Susanna; Benedetti, Simona; Saalia, Firibu K.; Carpen, Aristodemo; Manful, John; Johnson, Paa‐Nii T.; Barbiroli, Alberto; Bonomi, Francesco; Pagani, Ambrogina; Marti, Alessandra; et al.
Abstract : The development of innovative legume‐enriched rice products is a promising way to exploit rice varieties with a low sensory grade. In this work, a multidisciplinary approach was applied to the characterization of extruded breakfast cereals prepared from African‐grown Oryza glaberrima (cv. Viwonor) or Oryza sativa (cv. Jasmine 85) enriched with 30% cowpea flour, obtained from sprouted or nonsprouted cowpea. Regardless of the rice species, addition of sprouted cowpea flour conferred a peculiar volatiles profile, rich in sour, bitter, and astringent taste. Protein structural indices provided molecular insights about the macroscopic differences among samples. Extruded products from O. glaberrima were characterized by lower expansion rates with respect to those obtained from O. sativa, regardless of the type of cowpea flour. Sprouting time had a positive influence on the hardness of extruded glaberrima ‐based products, facilitating formation of a more compact matrix, but it did not influence sativa‐ based products. Therefore, the breakdown of protein during sprouting appeared fundamental for the incorporation of legume proteins in more compact matrices, such as the one from sativa rice. In the glaberrima ‐based products, addition of sprouted cowpea resulted in further loosening of the structure, and this was more evident at increased sprouting times.